2014
DOI: 10.2147/hp.s54404
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factor-mediated induction of WISP-2 contributes to attenuated progression of breast cancer

Abstract: Hypoxia and the hypoxia-inducible factor (HIF) signaling pathway trigger the expression of several genes involved in cancer progression and resistance to therapy. Transcriptionally active HIF-1 and HIF-2 regulate overlapping sets of target genes, and only few HIF-2 specific target genes are known so far. Here we investigated oxygen-regulated expression of Wnt-1 induced signaling protein 2 (WISP-2), which has been reported to attenuate the progression of breast cancer. WISP-2 was hypoxically induced in low-inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…We previously reported a HIF-2 specific regulation of WISP-2 expression in breast cancer cells [ 35 ]. Because WISP-2 is a known ERα target gene [ 36 ], we aimed for the analysis of the cooperation between estrogen and oxygen signaling.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported a HIF-2 specific regulation of WISP-2 expression in breast cancer cells [ 35 ]. Because WISP-2 is a known ERα target gene [ 36 ], we aimed for the analysis of the cooperation between estrogen and oxygen signaling.…”
Section: Resultsmentioning
confidence: 99%
“…SOD3/HIF-2α appears to trigger WNT activation through the autocrine secretion of specific WNT ligands. HIF-2α also transactivates the WISP2 promoter in human EC, 37 which suggests a common regulatory mechanism in humans. Analyses in human CRC support this hypothesis, as SOD3 levels correlated with the percentage of β-cateninstained EC.…”
Section: Sod3/hif-2α/wnt Pathway Induces Laminin α4mentioning
confidence: 93%
“…21 A search for genes whose expression has been reported specifically regulated by HIF-2α identified six potential candidates (including VEC) by which SOD3 might regulate T cell transmigration. We focused on WNT1inducible signaling pathway protein 2 (WISP2/CCN5), a non-conventional WNT ligand of the CCN (cysteine-rich 61 (Cyr61/CCN1)/connective tissue growth factor (CTGF/ CCN2)/nephroblastoma overexpressed gene (NOV/ CCN3)) family, since WISP2 modifies the perivascular environment through its interaction with the integrin α v β 3 35 36 ; WISP2 also modulates the immune cell infiltrate in breast tumors, 37 although to our knowledge, specific effects on T cell migration have not been described.…”
Section: Sod3-hif-2α Upregulates Wnt Ligands In Ecmentioning
confidence: 99%
“…CCN5 has been implicated as having an important role in carcinogenesis, with particular relevance to human breast disease [ 38 , 41 , 45 48 ]. In most studies, CCN5 expression has been shown to correlate inversely with the aggressiveness of cancers in breast [ 38 , 49 , 50 ], pancreas [ 51 , 52 ], salivary gland [ 53 ], gallbladder [ 54 ] and gastric tissue [ 55 ], suggesting tumor suppressor/anti-invasive activity [ 38 , 41 , 52 ]. Thus, at least in BC, CCN5 can be considered a good prognostic marker [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…CCN5 regulation in ER-α-positive cells is estrogen, an insulin-like growth factor and HIF-α2-dependent, and its expression has been found to participate in controlling proliferation as well as the aggressive phenotypes of these cells [ 38 , 44 , 50 ]. Thereby, CCN5 depletion in ER-α-positive cells promotes estrogen-independent growth, epithelial-mesenchymal transition (EMT), and stemness, consistent with more invasive phenotypes and display similarities to TNBC.…”
Section: Introductionmentioning
confidence: 99%